The Speech “Bamana”: Using the Syllable Repetition Task to Identify Underlying Phonological Deficits in Children With Speech and Language Impairments. - Roepke, Elizabeth; Bower, Kathryn E.; Miller, Catherine A.; Brosseau-Lapré, Françoise (Journal of Speech, Language & Hearing Research, 2020)
Purpose: This study compared performance on the Syllable Repetition Task (SRT) by preschoolers with diverse speech and language abilities to identify underlying impairments in speech processes. Method: Three groups of 13 children ages 4 and 5 years with (a) typically developing (TD) speech and language, (b) speech sound disorder (SSD), and (c) comorbid developmental language disorder and speech sound disorder (DLD + SSD) completed the SRT. We calculated competence, memory, encoding, and transcoding scores, as well as word-initial stress pattern and vowel accuracy. Results: A 3 × 3 (Group × Syllable length) factorial multivariate analysis of covariance revealed group differences for all measures and syllable length differences for memory, transcoding, and competence. There were no interactions between group and syllable length. TD children obtained the highest scores on each measure, though children with DLD + SSD performed similarly to TD children on encoding when vocabulary was included as a covariate. Children with SSD only outperformed children with DLD + SSD on competence and transcoding, and these two groups performed similarly on memory. A separate exploratory analysis using a 3 × 3 multivariate analysis of covariance revealed that children with DLD + SSD were more likely than children in the other groups to produce weak wordinitial stress and vowel errors during syllable repetition. Conclusion: Children with SSD and DLD + SSD exhibit underlying phonological deficits on the SRT compared to TD children. Results support the claim that memory and encoding are deficits in SSD. In addition, transcoding deficits were identified among children with no known oromotor impairment. Therefore, more research is required to identify the relationship between SRT performance and explicit measures of phonological processing.